Pengaruh Kualitas Pelayanan Dan Promosi Digital Terhadap Minat Beli Kunin Daster Yogyakarta - Septi Ayu Victoriadita (JURNAL EKOBIS DEWANTARA, 2023)
The purpose of this test is to examine: (1) does service quality influence purchase intention, (2) does digital promotion affect purchase intention, (3) does service quality and digital promotion affect purchase intention of Kunin Daster. The sample in this test is a customer who has made a purchase at Kunin Daster with only 100 respondents using a purposive sampling technique. The instrument in this test is a questionnaire that has been tested for validity and reliability using Alpha Cronbach. The data analysis method used is multiple linear regression using the SPSS version 26 data processing program. The test results originate from multiple linear tests showing that: (1) service quality has a positive effect on purchase intention, with partial test results showing t count points 2.208 > t table 1.984 and sig. 0.030 <0.05 ; (2) promotion has a positive effect on buying interest, with t count 5.544 > t table 1.984 and sig. 0.000 <0.05 ; (3) service quality and digital promotion simultaneously have a positive effect on purchase intention, with a calculated F point of 52.725 > F table of 3.09 and a significance point of 0.000 <0.05.